Effect of Giving Ethanol Extract of Robusta Coffee Beans (Coffea canephora Pierre ex A. Froehner) Based on Immunohistochemical Examination of GLUT-4 Protein Expression in White Rats (Rattus norvegicus) Model of Diabetes Mellitus - Jasmiadi; Rusman; Nur Alim; Tarisa Jabal Rahma (Jurnal Penelitian Pendidikan IPA, 2025)
Metabolic disorders are characterized by an increase in blood sugar due to a decrease in insulin secretion by pancreatic beta cells. Cells are unable to stimulate glucose absorption in muscle and fat tissue. The presence of GLUT-4 can increase the rate of glucose entry into insulin target tissues. The chlorogenic acid compound in robusta coffee beans is believed to lower blood glucose levels by activating GLUT-4. The aim of the research was to determine the effect of administering ethanol extract of robusta coffee beans (Coffea canephora Pierre ex A. Froehner) based on immunohistochemical examination of GLUT-4 protein expression in mice (Rattus norvegicus) with Type 2 Diabetes Mellitus. The research method included extraction by maceration with 96% ethanol: distilled water (3:7) solvent and immunohistochemical testing of the effect of ethanol extraction of Robusta coffee beans on mice. Rats were divided into 5 treatment groups, namely, Na-CMC 1%, metformin, 150 mg/kg BB, 300 mg/kg BB and 450 mg/kg BB and fed a high-fat diet for 6 months and immunohistochemical examination of skeletal muscle tissue was carried out. The results of immunohistochemical examination found that protein expression occurred in the positive control of coffee bean ethanol extract at doses of 150 mg/kg BB, 300 mg/kg BB and 450 mg/kg BB. The statistical test results show that the ethanol extract of robusta coffee beans at doses of 150 mg/kg BB, 300 mg/kg BB and 450 mg/kg BB is significant with the negative control      Na-CMC 1% but with the positive control metformin the three doses of ethanol extract of robusta coffee beans are not significant. From the discussion above, it can be concluded that the ethanol extract of robusta coffee beans has an effect at doses of 300 mg/kg BB and 450 mg/kg BB